1993
DOI: 10.2307/3283511
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Schistosoma bovis in Sheep Induced by an Experimental Fasciola hepatica Infection

Abstract: Sheep infected with Fasciola hepatica for 10 wk acquired a substantial level of resistance to challenge with Schistosoma bovis. The worm burden was reduced by 87.2% (P < 0.01) compared with that of a control group. But when sheep primarily were infected with S. bovis and 6 wk later with F. hepatica, no significant reduction in the S. bovis burden was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…A variety of biological activities such as secretion of cytokines and lysis of target cells have been ascribed to CC15 gd T cells (Abbas et al, 1994), whose expression has been also described in caprine S. bovis schistosomiasis (Lindberg et al, 1999). Likewise, our histopathological findings agree with parasitological findings (Rodríguez-Osorio et al, 1993) which indicated that F. hepatica did not have an influence on an established S. bovis infection. However schistosome-infected sheep resistant to challenge with F. hepatica when there was no deposition of schistosome eggs in the liver tissue at the time of challenge, have been described .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A variety of biological activities such as secretion of cytokines and lysis of target cells have been ascribed to CC15 gd T cells (Abbas et al, 1994), whose expression has been also described in caprine S. bovis schistosomiasis (Lindberg et al, 1999). Likewise, our histopathological findings agree with parasitological findings (Rodríguez-Osorio et al, 1993) which indicated that F. hepatica did not have an influence on an established S. bovis infection. However schistosome-infected sheep resistant to challenge with F. hepatica when there was no deposition of schistosome eggs in the liver tissue at the time of challenge, have been described .…”
Section: Discussionsupporting
confidence: 87%
“…Also, protection against S. bovis infection induced by a primary infection with Fasciola gigantica (Yagi et al, 1986) or a previous immunization with a fatty acid-binding protein from F. hepatica (Fh12) (Aban et al, 1999), has been described in calves and mice, respectively. Similarly, Rodríguez-Osorio et al (1993) showed that sheep infected with F. hepatica acquired resistance to challenge with S. bovis with a significant reduction in the S. bovis burden. As cited above, in the literature reviewed the relationship between Schistosoma spp.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…An enhanced resistance against F. hepatica and F. gigantica after primary infection with S. bovis has been described in cattle (Sirag et al, 1981;Yagi et al, 1986) and sheep . These findings imply that these two trematodes may be susceptible to the same or similar immune responses (Spithill et al, 1999) and may have common antigens (Rodriguez-Osorio et al, 1993). These findings imply that these two trematodes may be susceptible to the same or similar immune responses (Spithill et al, 1999) and may have common antigens (Rodriguez-Osorio et al, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…A vaccine appears as a very valuable additional complement to mass chemotherapy in long-term disease control strategy. Vaccination is based on the partial resistance developed against the natural infection, the protection induced by irradiated cercariae and the cross-resistance stimulated by other flukes as Fasciola hepatica (Hewitson et al, 2005;Rodríguez-Osorio et al, 1993;Vercruysse and Gabriel, 2005).…”
Section: Introductionmentioning
confidence: 99%